Sistem Informasi Geografis Sumur Bor Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Lombok Tengah Berbasis Web - M.Gunawan Ridho Pribadi; Wire Bagye (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
The Public Works and Spatial Planning Office of Central Lombok Regency is one of the government agencies responsible for determining the addresses and coordinates of drilled wells in the area. Currently, data for the construction of drilled wells in Central Lombok Regency still uses a conventional system in which the data and information needed for the process of constructing drilled wells are recorded physically on paper documents. The drilled well data consists of coordinates, depth, location, work CV, and costs. If employees need drilled well data to compile reports, it takes a relatively long time. Therefore, to increase time efficiency, an information system website for the construction of boreholes was built at the Public Works and Spatial Planning Office of Central Lombok Regency using the Waterfall method.